2015
DOI: 10.3340/jkns.2015.57.6.465
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Hemangioblastoma in the Pituitary Stalk: A Case Report and Review of the Literature

Abstract: Hemangioblastomas in the pituitary stalk are especially rare. Most pituitary stalk hemangioblastomas reported in the literature were associated with von Hippel-Lindau (VHL) disease. Here, we report only the 3rd case of sporadic pituitary stalk hemangioblastoma diagnosed in a 60-year-old woman. Despite the danger of potential complications due to excessive vascularity or proximity to important neural structures, the tumor in our case was successfully removed while preserving pituitary function. In this case, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Pituitary stalk hemangioblastomas are strongly associated with VHL disease and their occurrence outside the VHL syndrome is a rare phenomenon. To our best of knowledge, after searching Pubmed/MEDLINE, only nine sporadic cases of pituitary stalk hemangioblastomas, including our case were found (summarized in Table 1) [10][11][12][13][14][15][16][17][18][19][20]. In general, pituitary stalk hemangioblastomas are indistinguishable from craniopharyngiomas based on MRI findings, making the preoperative diagnosis of hemangioblastoma extremely challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary stalk hemangioblastomas are strongly associated with VHL disease and their occurrence outside the VHL syndrome is a rare phenomenon. To our best of knowledge, after searching Pubmed/MEDLINE, only nine sporadic cases of pituitary stalk hemangioblastomas, including our case were found (summarized in Table 1) [10][11][12][13][14][15][16][17][18][19][20]. In general, pituitary stalk hemangioblastomas are indistinguishable from craniopharyngiomas based on MRI findings, making the preoperative diagnosis of hemangioblastoma extremely challenging.…”
Section: Discussionmentioning
confidence: 99%
“…HBLs enhance more strongly with contrast than pituitary tumor and contrast-enhanced coronal T1-weighted images generally identify the diaphragm sella between the tumor and pituitary gland in suprasellar HBLs [1011]. Lee et al [12] reported a case of sporadic HBL in the pituitary stalk and reviewed the literature that among 14 cases of HBLs in the pituitary stalk, only 3 cases are not associated with VHL disease. However, they were able to discriminate HBLs and other tumorous condition preoperatively because the mass was beyond the diaphragm sella and absent dural tail sign, a characteristic finding of meningioma [12].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [12] reported a case of sporadic HBL in the pituitary stalk and reviewed the literature that among 14 cases of HBLs in the pituitary stalk, only 3 cases are not associated with VHL disease. However, they were able to discriminate HBLs and other tumorous condition preoperatively because the mass was beyond the diaphragm sella and absent dural tail sign, a characteristic finding of meningioma [12]. The onset of the disease is usually a differential point with craniopharyngioma.…”
Section: Discussionmentioning
confidence: 99%
“…5 Total removal and lower removal rates show obvious differences in outcome. Although an exceptional case of successful removal of the tumor with preservation of the pituitary stalk was reported, 16 dissection must be performed quite prudently, and intentional sectioning should be performed without hesitation in cases of excessive bleeding. Experimental investigation of disturbances in pituitary function revealed that sectioning at the distal portion from the hypothalamus resulted in less dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Only 12 previous cases of suprasellar hemangioblastoma were identified as VHLD-unrelated sporadic cases (including two suspected cases). [5][6][7][8][9][10][11][12][13][14][15][16] However, all these cases were only diagnosed based on clinical screening and confirmation of family history.…”
Section: Introductionmentioning
confidence: 99%